Evaluasi Kebijakan Alokasi Dana Desa dalam Pelaksanaan Pembangunan di Desa Kuta Kecamatan Pujut Lombok Tengah - Lalu Aksar Hadi; Pramudiana, Ika Devy (Soetomo Magister Ilmu Administrasi, 2025)
The research written by this researcher aims to know and analyze the government policies of Kuta Village, Pujut District, Central Lombok Regency in making policies related to the allocation of Village Funds to development and its supporting and inhibiting factors. The research written by the researcher is a type of qualitative research and uses a descriptive approach. The theory used in this study is Public Policy Evaluation according to William Dunn with six Criteria, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. As for data collection, the researcher is carried out through observation, interviews, document studies, then analyzing the data used is data collection, data condensation, data presentation, and drawing conclusions The results of the study found that the Evaluation of Village Fund Allocation Policy in Development in Kuta Village, Pujut District, Central Lombok Regency was in accordance with the theory used. That in the Effectiveness criterion, it is still said that it is not effective in using village funds for development. In the efficiency criterion it was found that the Kuta village government was inefficient in allocating village funds for development, in the adequacy criterion it was found that it was still not enough even though only a few were found to be successful in building but this was not fully achieved or even less, the equality criterion was found to be still uneven, the Responsiveness criterion was found that in the development program in Kuta Village it was responded well but completely has not been realized, The last criterion is accuracy, it was found that several development programs in Kuta Village only met the criteria. The supporting factor for the evaluation of the village fund allocation policy in development in Kuta Village is the strong role of ITDC as a tourism manager in Kuta Village because the Kuta Village Area is included in the Special Economic Zone (SEZ). On the other hand, there is also some support from the community, but it is only a few percent of the total population of Kuta Village. The inhibiting factors are 1) Lack of coordination with several institutions and with the community. One of them is the lack of coordination with ITDC, 2) The Kuta Village government bureaucracy, often occurs in the development planning process there are personal interests from the village apparatus so that many mistakes occur due to the personal interests of the Kuta village government bureaucracy in managing village funds for development, 3) The last inhibiting factor is Covid-19, the Covid-19 phenomenon is still an inhibiting factor for Kuta Village to carry out development because of some village funds distributed for direct cash assistance (BLT) in accordance with the circular letter of the Ministry of Finance of the Republic of Indonesia.